Physical Fitness Levels Based on the 12-Minute Running Test in Medical Undergraduate Cadets at the Republic of Indonesia Defense University, Cohort 4 of the Year 2023 - Trevicko Mahottama Ardiansyah; Syahnadira Puspita Handandari; Adinda Ratulia Suwarno; Salsabila Azka; Mozart Mozart; Vireza Pratama; Deity Nugraha; Elies Fitriani (Bali Medical and Wellness Journal, 2024)
Objective: Physical fitness plays a critical role in maintaining the health and performance of medical undergraduate students, particularly at the Republic of Indonesia Defense University (RIDU), where academic studies intersect with military training. This study aims to describe the physical fitness levels of medical undergraduate cadets based on the results of the 12-minute running test (Cooper Test) and their self-reported physical activity levels using the Global Physical Activity Questionnaire (GPAQ). Methods: We employed a descriptive survey research method. The study included 72 respondents from the 2023 cohort 4 student population. Results: Physical Activity Levels: The majority of respondents reported a heavy level of physical activity (87.5%). Physical Fitness Levels: Overall, respondents demonstrated a sufficient level of physical fitness (73.6%). Gender and Age: No significant differences were observed in the distribution of physical fitness levels based on gender or age. Conclusion: Most cadets enrolled in undergraduate medical study programs at RIDU exhibit an adequate level of physical fitness.